Children’s right to participate in early childhood care and education settings and relative innovatory supportive digital tools for ECCE professionals’ development - Stavropoulos, E. (2022)
Young children’s participation is key to developing a culture of human rights, democracy, and rule of law and according to Council of Europe (2017) and United Nations (2005). In these terms, children’s right to participate is described as a key aspect in the framework of educational quality, and the positive relationship between children’s right to participate and early childhood care and education (ECCE) quality is already documented. Although this concept is not new to ECCE professionals, its application seems to remain a challenge within everyday activities. It is thus important for ECCE professionals to reflect on this right and on the practices towards its promotion, in order to be able to supply high quality education. The paper presents the innovatory attempts regarding the digital tools developed within the PARTICIPA Erasmus+ project (Professional development tools supporting participation rights in early childhood education) aiming to involve three target group -directors, teachers and teachers’ assistants- working in all types of early childhood care and education settings, so that have a digital space to reflect about children’s right to participate and its implementation. More specifically, the paper presents (a) a training program targeting the ECCE settings’ professionals provided through a massive open online course (MOOC) in 5 languages and disseminated in an online learning platform, focusing on the theoretical and practical aspects of children’s right to participate (i.e., state of the art, relevant pedagogical practices), (b) toolkits (i.e., validated self-assessment questionnaires) for ECCE directors and teachers and teacher assistants supported by discrete qualitative studies.